Phosphorylation of Smad2/3 at the specific linker threonine residue indicates slow-cycling esophageal stem-like cells before re-entry to the cell cycle. Issue 2 (30th September 2016) - Takahashi, Y.; Fukui, T.; Kishimoto, M.; Suzuki, R.; Mitsuyama, T.; Sumimoto, K.; Okazaki, T.; Sakao, M.; Sakaguchi, Y.; Yoshida, K.; Uchida, K.; Nishio, A.; et al.
Summary: The stem cell compartment in the esophageal epithelium is possibly located in the basal layer. We have identified significant expression of Smad2/3, phosphorylated at specific linker threonine residues (pSmad2/3L-Thr), in the epithelial cells of murine stomach and intestine, and have suggested that these cells are epithelial stem cells. In this study, we explore whether pSmad2/3L-Thr could serve as a biomarker for esophageal stem cells. We examined esophageal tissues from normal C57BL/6 mice and those with esophagitis. Double immunofluorescent staining of pSmad2/3L-Thr with Ki67, CDK4, p63, or CK14 was performed. After immunofluorescent staining, we stained the same sections with hematoxylin-eosin and observed these cells under a light microscope. We used the 5-bromo-2-deoxyuridine (BrdU) labeling assay to examine label retention of pSmad2/3L-Thr immunostaining-positive cells. We collected specimens 5, 10, 15 and 20 days after repeated BrdU administrations and observed double immunofluorescent staining of pSmad2/3L-Thr with BrdU. In the esophagus, pSmad2/3L-Thr immunostaining-positive cells were detected in the basal layer. These cells were detected between Ki67 immunostaining-positive cells, but they were not co-localized with Ki67. pSmad2/3L-Thr immunostaining-positive cells showed co-localization with CDK4, p63, and CK14. Under a light microscope, pSmad2/3L-Thr immunostaining-positive cells indicated undifferentiated morphological features. Until 20 days follow-up period, pSmad2/3L-Thr immunostaining-positive cells were co-localized with BrdU. pSmad2/3L-Thr immunostaining-positive cells significantly increased in the regeneration phase of esophagitis mucosae, as compared with control mice (esophagitis vs. control: 6.889 ± 0.676/cm vs. 4.293 ± 0.659/cm; P < 0.001). We have identified significant expression of pSmad2/3L-Thr in the specific epithelial cells of murine esophagi. We suggest that these cells are slow-cycling epithelial stem-like cells before re-entry to the cell cycle.